Simplicity and the art of something more: A cognitive–semiotic approach to simplicity and complexity in human–technology interaction and design experience - Rousi, Rebekah; Silvennoinen, Johanna (Human Technology, 2018)
In human–technology interaction, the balance between simplicity and complexity has been much discussed. Emphasis is placed on the value of simplicity when designing for usability. Often simplicity is interpreted as reductionism, which compromises both the affective nature of the design and usability itself. This paper takes a cognitive–semiotic approach toward understanding the dynamics between the utilitarian benefits of simplicity in design and the art of something more: considerate complexity. The cognitive–semiotic approach to human–technology design experience is a vehicle for explaining the relationship between simplicity and complexity, and this relationship’s multisensory character within contemporary art-design, information technology product design, and retail design. This approach to cognitive semiotics places emphasis on the design, object, mental representation, and the qualitative representation. Our research contributes on the levels of theoretical development and methodology, having direct design implications through articulating that simplicity exists as the careful organization of complex elements.